2010
DOI: 10.1002/nml.257
|View full text |Cite
|
Sign up to set email alerts
|

Building a better workplace for teen volunteers through inclusive behaviors

Abstract: Facing a decline in the number

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Specifi cally for fundraising, Waters (2008) found that major gift donors evaluate their relationship with nonprofi t organizations more favorably than annual giving donors, and repeat donors valued the relationship more than one-time donors. Similar results have been found for volunteers ( Waters and Bortree, 2010 ), association members ( Ki and Hon, 2009 ), and consumers ( Hall, 2006 ). Public relations scholarship has yet to examine the relationship measures with perhaps an organization ' s most important public, its employees.…”
Section: Organization -Public Relationshipssupporting
confidence: 67%
See 1 more Smart Citation
“…Specifi cally for fundraising, Waters (2008) found that major gift donors evaluate their relationship with nonprofi t organizations more favorably than annual giving donors, and repeat donors valued the relationship more than one-time donors. Similar results have been found for volunteers ( Waters and Bortree, 2010 ), association members ( Ki and Hon, 2009 ), and consumers ( Hall, 2006 ). Public relations scholarship has yet to examine the relationship measures with perhaps an organization ' s most important public, its employees.…”
Section: Organization -Public Relationshipssupporting
confidence: 67%
“…The purpose of this question was to understand how employees perceived their levels of satisfaction, commitment, control mutuality, and trust with the organization. Previous organization -public relations have found that donors ( Waters, 2010 ), volunteers ( Waters and Bortree, 2010 ) and association members ( Ki and Hon, 2009 ) all found that their respective study participants evaluated their relationships with nonprofi t organizations positively on all four relationship indicators. Sadly, most of the HBCU fundraisers did not evaluate their relationship with their employers highly.…”
Section: Discussionmentioning
confidence: 78%
“…However, as indicated by the research of Handy and Srinivasan (2005), this process is complex, and other nonmonetary factors come into play such as tradition, the good will that volunteers bring to an organization, and roles that are either prescribed for volunteer board members by law or those that are prescribed for paid employees through union agreements (Handy et al 2008;Ontario Hospital Association 1988). Other factors that can come into play and bear upon an organization' s decision to use volunteers are the adequacy of the volunteer supply (Hager and Brudney 2011); the employees' past experience with volunteers (Rogelberg et al 2010), including the extent to which paid and volunteer leaders share the organization's goals (Solansky, Duchon, Plowman, and Martínez 2008); the extent to which the volunteers trust the organization (Waters and Sevick Bortree 2010); and how volunteers are managed by the organization (Leonard, Onyx, and Hayward-Brown 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, media relations efforts have been tied to increases in donations to nonprofits (O'Neil, 2007;Waters and Tindall, in press), increased volunteerism (Garner and Garner, 2010;Waters and Bortree, 2010), and greater participation in a nonprofit organization's programs and services (Patterson and Radtke, 2009). Research has shown that American foundations have even been able to tap into the power of the media through their media relation efforts to create social and policy changes (Wymer and Sridhar, 2003;Dolcinar and Lazarevski, 2009).…”
Section: Introductionmentioning
confidence: 98%